E-service portal for freelance community: case study in photography business - Supaporn Chai-Arayalert; Supattra Puttinaovarat; Nattaporn Thongsri (Institute of Advanced Engineering and Science, 2022)
This study revealed the limitations of freelancers’ inability to perform portfolios and biographies, their performance ratings to a large community of customers. The difficulties were evident in searching for reliable, qualified and experienced freelancers from multi-channel information sources. These limitations might impact the ability of freelancers selected by customers to perform the required task to the customers’ satisfaction. This research focused on the case study of the freelance community for photography business in southern of Thailand. This aims to establish an online facility in which freelance photographers can publicize their services and performance to potential customers. The concepts entailed in web portals and e-services were the key elements in the development and ensured that its functions worked efficiently. The study employed qualitative methods were used to assess the current practices of web portal and thus determining the requirements for the e-service web portal for freelance community. The practical contribution is that it can aid the effective design and implementation of an e-service web portal for the freelance community of photography business, and it is a massive step towards promoting the freelance community in Thailand.